DYRK1B inhibition exerts senolytic effects on endothelial cells and rescues endothelial dysfunctions - Pramotton, Francesca M.; Abukar, Asra; Hudson, Chantelle; Dunbar, James; Potterton, Andrew; Tonnicchia, Simone; Taddei, Andrea; Mazza, Edoardo; Giampietro, Costanza (Mechanisms of ageing and development, 2023)
Aging is the major risk factor for chronic disease development. Cellular senescence is a key mechanism that triggers or contributes to age-related phenotypes and pathologies. The endothelium, a single layer of cells lining the inner surface of a blood vessel, is a critical interface between blood and all tissues. Many studies report a link between endothelial cell senescence, inflammation, and diabetic vascular diseases. Here we identify, using combined advanced AI and machine learning, the Dual Specificity Tyrosine Phosphorylation Regulated Kinase 1B (DYRK1B) protein as a possible senolytic target for senescent endothelial cells. We demonstrate that upon induction of senescence in vitro DYRK1B expression is increased in endothelial cells and localized at adherens junctions where it impairs their proper organization and functions. DYRK1B knock-down or inhibition restores endothelial barrier properties and collective behavior. DYRK1B is therefore a possible target to counteract diabetes-associated vascular diseases linked to endothelial cell senescence. •DYRK1B protein is a new possible senolytic target for senescent endothelial cells.•DYRK1B upregulation in senescent endothelial cells impairs adherens junction organization and functions.•Dyrk1B knockdown or inhibition with senolytics restores endothelial barrier properties and collective cell behavior.